Investigation on Phytochemical and Antimicrobial Properties of Andrographis Paniculata - G. Durgadevi, K. Kolanjinathan (International Journal of Modern Agriculture, 2020)
Marine microbes signify a capable source of beneficial products expecting unearthing for the inhibition or handling of numerous pathogens. In this research article the bio active complex between marine isolate and well known herbal Antrographis paniculata was synthesized by active fraction that showed maximum activity on total antioxidant and DPPH in dose dependent manner. The bio active complex ratio (5:5) showed antibacterial potency at low dose against Salmonella typhi and E. coli with zone of inhibition 21mm and 20mm respectively. The synergistic activity can be achieved by the complexation between marine and herbal sources.